Analisis Kemitraan Dalam Pengelolaan Desa Wisata Kandri Kecamatan Gunungpati Kota Semarang - Yuliana Isnaningtyas; Fitriyah .; Neny Marlina (Journal of Politic and Government Studies, 2017)
Kandri, in Gunungpati subdistrict, is one of the the three village, that wasdecided as the tour villages, as stated in the decree of Semarang Mayor in 2012. Theestablishment of the Kandri tour village is aimed to improve the potency of people inKandri to create the economic independence through tourism sector. This research isaimed to analyze the parthnership in the management of the Kandri tour village inGunungpati subdistrict.The research method used is a qualitative approach, and the data collectiontechniques used are documentation, observation and interview. The source of the researchare Department of culture and tourism of Semarang, Kandri village, Pandanaran andSukomakmur tourism awareness group and people in Kandri.The result of the research shows that the Pandanaran tourism awareness group isthe one which has responsibility of the managemanet of the tour village. It is the actorwhich has the center role in creating the improvement of the Kandri tour village. All theinvolved elements have done their duty and function well so that the people gain the benefitdirectly and indirectly. The partnership in Kandri tour village is a psudeo parthnership thatis appropriate to the condition in the village. Yet, the parthnership is usual and notsustainable. Most of the partnership is done through CSR given by the private institution tothe people in Kandri through group of torism awareness. It also involves the government,acadmy and society.Keywords : Tour village, management, parthnership